Структура системы Enterprise Performance Management с учётом технологии каскадирования ключевых показателей деятельности - Москаленко, Валентина Владимировна; Фонта, Наталья Григорьевна (НТУ "ХПИ", 2016)
Приведена технология каскадирования стратегических показателей и обоснование включения её как отдельный модуль в систему Enterprise Performance Management. Сформирована задача стратегического развития и представлена структура программы развития предприятия. Представлена структура EPM-системы. В рамках EPM-системы описаны подсистемы стратегического планирования и каскадирования. Рассмотрены вопросы использования ETL-технологий при построении EPM-системы, определены задачи, которые решаются при проектировании процессов преобразования данных.

The technologies of cascading for the strategic indicators and substantiation of its inclusion as a separate module in the Enterprise Performance Management system were performed. Strategic task of elaboration was formed and the structure of program of the enterprise development was represented. The concept for technology of cascading of the key performance indicators on the enterprise is described. Separation of key performance indicators to the operating, investing and financing activities are invited to consider in the process of cascading. The structure of EPM-system is presented. The subsystems for strategic planning and cascading are described as the parts of the EPM-system. The modules that determines the performance of business processes operating, investing and financing activities and the module that calculates the performance indicators of these activities are included in the cascading subsystem. The problem of the using of the ETL-technologies for constructing EPM-system was resolved, tasks that are solved with the design of the data conversion process, were determine. Particularities of the ETL-tools using for the being developed EPMsystem were allocated.
Structure of Enterprise Performance Management System that takes into account the technology of the cascading of key performance indicators
Keywords: стратегическое управление; стратегическое планирование; бюджетирование; EPM-система; ETL-технологии; strategic management; cascading; budgeting; EPM-system; ETL-technology